Social determinants approaches to public health : from concept to practice - Blas, Erik (WHO GenevaCH, 2011)
Describes experiences with implementing public health programmes that intend to address social determinants and to have a great impact on health equity. Documents the real-life challenges in implementing such programmes, including those in scaling up, managing policy changes and intersectoral processes, adjusting design and ensuring sustainability.